Detalhamento dos impostos estaduais indicados na Emenda Constitucional nº. 29 para financiar a saúde pública no Estado do Amazonas - (:unkn) unknown (Universidade Federal do Amazonas, 2008)
This paper presents a different analysis of the public health financing in the State of Amazonas, through revenue from state taxes for that purpose by Constitutional Amendment No 29, linked minimal amount of municipal, state and Union revenues, to costs payment from public health actions and services. The presented form, both in the Annual Budget Law, as in the General Balance of the State of Amazonas, shows the applied values in the public health financing in order totalized, to prevent from knowing the real amount applied from taxes. The essence of the public budget is revenue genereted from the police power assigned to the public authority, obtained from the society and costs that must meet the demands of that society. To prove the usage of each tax was applied the decomposition method of the resources source contains the revenue origin eliminating this way any kind of constitutional and legal deduction occurred over taxes.Thus it was possible to demonstrate the liquid value of each tax over mandatory percentage is applied to compose the financing.The prediction of all existing revenues and the establishment of all costs are found in Annual Budget Law. Inicialy, are demonstrated what must be applied at health services and actions financing, because, the values that consists the law are forecasts. In the State General Balance is shown what was actually collected in all revenue displayed inicialy in the law and others raised during the financial year. Of the values collected are discounted the constitutional and legal deductions to gain the liquid value. After this discount operation, the mandatory percentage is applied and is demonstrated the value that was destinated to public health costs payment of each tax. thus shown it is possible, for both to internal control entities as external control and society to inspect the correct enforcement of these resources
Keywords: Saúde pública - Amazonas; Políticas de saúde - Amazonas; Financiamento governamental; Emenda Constitucional nº. 29; Detalhamento de impostos; CIÊNCIAS SOCIAIS APLICADAS